Exploring effect of chitosan on antioxidant system and hypericin content in Hypericum perforatum L. under various irrigation regimes - Rayhaneh Amooaghaie; Nafiseh Rajaie (BMC Plant Biology)
Abstract The beneficial effects of chitosan on stress tolerance and secondary metabolism have been documented in a few medicinal plants. However, the impact of chitosan on water deficit tolerance in St John’s Wort (Hypericum perforatum L) remains largely unknown. Therefore, a field experiment was executed to assess the effect of foliar spraying various chitosan concentrations (0, 100, 200, and 400 mg L−1) under irrigation intervals 7 (normal), 10 (mild water stress), and 13 (severe water stress) days. When irrigation intervals increased, biomass substantially decreased in both harvests. However, hypericin content increased at mild water stress, whereas it decreased under severe water stress. Foliar application of chitosan increased biomass, total phenol content )TPC( and hypericin content under all irrigation intervals. The highest hypericin content and TPC were verified by spraying 200 mg L−1 chitosan under the mild water stress that corresponded with the most 2,2-diphenylpicrylhydrazyl (DPPH) scavenging activity in the leaves. The foliar application of chitosan improved relative water content, chlorophyll a, b contents and decreased the content of H2O2 and malondialdehyde in plants grown under irrigation intervals of 10 and 13 days. The compensatory effect of chitosan was due to enhancing the activities of catalase and peroxidase and increasing proline content in leaves. However, 400 mg L−1 of chitosan negatively affected most of the aforementioned attributes in St John’s Wort. Collectively, the results indicate that foliar spraying with an appropriate concentration of chitosan may be a promising solution for improving the productivity and pharmaceutical value of medicinal plants under water deficit.